Metrology of Rectangular Distance in Wireless Keyboard: A Repeatability Study - Muhammad Harith Ismail; Ibrahim Masood (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study explores the use of metrology in manufacturing, specifically for measuring rectangular part assemblies which is a wireless keyboard. This study aims to identify the critical-to-quality (CTQ) features and its related variables in a wireless keyboard, and evaluate its repeatability of the CTQ variable measurement when dealing with contact-based and non-contact-based measuring method. This work has major implications for improving industrial quality control, minimising production mistakes, and giving practical approaches for industry practitioners and academics. It emphasizes using Geometric Dimensioning and Tolerancing (GD&T) to improve measurement accuracy and adhere to industry standards through Feature Control Frames. The findings are vital for enhancing industrial quality control by providing methods to reduce errors and optimize production processes. This research paper offers practical guidance for industry professionals and academics alike, aiming to improve operational efficiency and ensure high-quality manufacturing. The potential economic benefits underscore the significance of these advancements in advancing manufacturing practices and contributing to overall economic growth.